Evolution of DevOps: Lessons learned for success as part of digital strategy - Silva-Atencio, Gabriel (2024)
The objective was to investigate the good practices that must be followed to implement DevOps culture to accelerate the development of software applications in shorter periods and unify the story so they can work hand in hand. The research was under a qualitative approach and a review of references to provide information on the terms and development methodologies used. Finally, to put DevOps into practice, it is necessary to understand that, even if you have the best tools available, if you do not have the culture, you will not get better results since it is a combination of good practices to be able to function. In this sense, to collaborate with this culture change, the support of trained leaders is essential, who support and sponsor the new way of working, where all areas of the company can be integrated.